Sparse arrays and image compounding techniques for non-destructive testing using guided acoustic waves - Prado, Vander Teixeira [UNESP]; Higuti, Ricardo Tokio [UNESP]; Kitano, Cláudio [UNESP]; Martínez-Graullera, Óscar (Springer Nature, 2013)
Piezoelectric array transducers applications are becoming usual in the ultrasonic non-destructive testing area. However, the number of elements can increase the system complexity, due to the necessity of multichannel circuitry and to the large amount of data to be processed. Synthetic aperture techniques, where one or few transmission and reception channels are necessary, and the data are post-processed, can be used to reduce the system complexity. Another possibility is to use sparse arrays instead of a full-populated array. In sparse arrays, there is a smaller number of elements and the interelement spacing is larger than half wavelength. In this work, results of ultrasonic inspection of an aluminum plate with artificial defects using guided acoustic waves and sparse arrays are presented. Synthetic aperture techniques are used to obtain a set of images that are then processed with an image compounding technique, which was previously evaluated only with full-populated arrays, in order to increase the resolution and contrast of the images. The results with sparse arrays are equivalent to the ones obtained with full-populated arrays in terms of resolution. Although there is an 8 dB contrast reduction when using sparse arrays, defect detection is preserved and there is the advantage of a reduction in the number of transducer elements and data volume. © 2013 Brazilian Society for Automatics - SBA.
Keywords: Lamb waves; Sparse arrays; Synthetic aperture techniques; Ultrasonic non-destructive testing; Compounding techniques; Guided acoustic waves; Inter-element spacing; Non destructive testing; Ultrasonic inspections; Acoustic waves; Acoustics; Nondestructive examination; Surface waves; Synthetic apertures; Transducers; Ultrasonic testing